A diasporic welcome integration of immigrants through spatial patterns Syrian Circassians in Düzce as a case study - Gökesaoğlu, Elmashan (İstanbul Bilgi Üniversitesi, 2019)
In the course of a globalizing world, the concept of migration has evolved dynamically with its branches extending towards multiple fields of social sciences embracing education, health, identity, employment and other socio-demographic issues. However, after brief reviews of literature, it has been observed that there are limited number of studies that focus on migration within the context of space and place –by space meaning; the tangible physical form of a city, village, street or a building and by place meaning; a homeland, motherland or a neighborhood after the factor of ‘inhabitants’/ human relations and social integration gets in the picture. In this sense, the initial purpose of this dissertation is to offer a meaningful synthesis of migration matters and spatial patterns of refugees. A comprehensive research is carried out to analyze the role of space and place during the integration and socialization processes of immigrants. Syrian Circassians in Düzce will be used as a sample case to track the wondered outcome of the research: can space and place –as an end in itself- play a facilitating / normalizing role through the challenging phases of migration?

Globalleşen dünyada, göç konsepti, sosyal bilimleri eğitimden, sağlığa, kimlik, istihdam ve diğer sosyo-demografik konulara uzanan birçok alandaki branşlarını kucaklayacak şekilde dinamik bir gelişim göstermektedir. Fakat, akademik literatürün özet taranması, göçü mekân ve yer kavramı çerçevesinde inceleyen- mekân kavramını; şehir, kasaba, cadde ve bir binanın somutlaşmış fiziksel formu, yer kavramını ise; memleket, anavatan veya komşuluk ilişkileri olarak ele alan, yerel halk/ insan ilişkileri ve sosyal entegrasyon konularının resme dahil olduğu sınırlı sayıda çalışma olduğu görülmektedir. Bu bağlamda, tezimizin başlangıç amacı göç konuları ve mültecilerin mekânsal paternleri ile ilgili anlamlı çıkarımlar yapmaktır. Göçmenlerin entegrasyon ve sosyalleşme süreçleri esnasında mekân ve yer kavramlarının rolü kapsamlı bir araştırma ile analiz edilmiştir. Düzce’deki Suriyeli Çerkezler, mekân ve yer kavramlarının- kendi içerisinde bir son olarak- göçün problemli safhalarında kolaylaştıran/normalleştirici bir rolü olup olmadığının inceleneceği örnek bir durum olarak kullanılacaktır.